Calitatea experienței subiective - Beca, Elena (Calitatea Vieții, 1994)
The quality of subjective experience reflects the degree of world coherence perceived by individuals during the process of socialization. An equilibrium between the human efforts aiming to change the objective context of experience and those aiming to change the subjective interpretation of experience is required in order to obtain the quality of subjective experience. A significant increase in this quality is achieved during the interiorisation of gratifications which justify the process of socialization. Varying between the cognitive dissonance and optimal experience, the quality of subjective experience makes possible the correction between the satisfactory character of an individual’s behavior with respect to his own expectations and socially accepted character of the same behavior.